A novel fully-programmable analog fuzzifier architecture for interval type-2 fuzzy controllers using current steering mirrors - Souza, Gabriel A. F.; Santos, Rodrigo B.; Rocha Rizol, Paloma M. S. [UNESP]; Oliveira, Duarte L.; Faria, Lester A. (Ios Press, 2018)
A novel analog fuzzy membership function generator architecture, based on current steering mirrors, for interval type-2 fuzzy controllers is proposed in this paper. The Footprint of Uncertainty (FOU), characteristic of an interval type-2 fuzzy set, is generated by this novel architecture, which uses current steering mirrors controlled by a voltage input and allows width variation based on a central line. This main feature makes the circuit inherently type-2, i.e., not dependent of any type-1 fuzzifier, unlike all previous analog fuzzifiers found in the literature. The circuit operates in current mode and is capable of generating trapezoidal, triangular, Z-shaped and S-shaped membership functions. Input currents allow shape configuration, whereas a digitally programmable current mirror provides different inclinations, making it fully programmable (shape, width of the FOU, inclination, and position). Simulations validating the architecture were performed with TSMC CMOS 0.18 mu m technology, in CADENCE software. The circuit was later fabricated and characterized. Experimental results confirmed its ability to work as a fuzzifier, with all specified features, showing to be suitable even for dedicated low power applications.
Keywords: Analog circuits; low-power; fuzzifier; interval type-2 fuzzy logic